Technology of scan reminder pro in cooling room / Mohammad Afif Akma Azmi, Siti Nur Shahida Razali and Nur Laila Adila Che Abdul Majid - Azmi, Mohammad Afif Akma; Razali, Siti Nur Shahida; Che Abdul Majid, Nur Laila Adila (Faculty of Plantation and Agrotechnology, 2023)
The harvested fruit should be stored in a cooling room to prevent the fruit from rotting. The purpose of this study is to examine the easy way workers operate the cooling room without any problems. Scan Reminder Pro is one of the technologies created from the combination of QR code and Calendar Reminder. It will also be automatically connected to an Android TV set up in front of the cooling room to give reminders about the temperature, the amount of fruit according to the maturity index, and the date the fruit will be removed from the cooling room. It makes it easier for workers to record the entry and exit dates of fruit stored in the cooling room. When the employee scans the QR code that has been placed on the side of the fruit collection basket, the data will be saved and will automatically be used as a reminder in the employee's phone. There are a few parties after the fruit is harvested and put into the cooling room without recording the fruit maturity index or mixing ripe and unripe fruit. In addition, some are not aware of the temperature or the date the fruit enters the cooling room. This step ensures that workers will know better the date the fruit is taken out of the cooling room. This technology can make it easier for workers in handling matters and can reduce damage to fruit if time management can be overcome well.